Pengaturan Pola Tanam Karet (Hevea brasiliensis Muell.Arg.) untuk Tumpang Sari Jangka Panjang - . Sahuri (Institut Pertanian Bogor, 2017)
Low prices of rubber have been a serious problem to rubber farmers. The rubber based intercropping system offers a practical solution to this issue and increasing overall productivity. This experiment was aimed to determine the suitable spatial arrangements in rubber planting to facilitate long-term rubber-based intercropping systems. A ﬁeld experiment was established in a smallholder rubber plantation in the Tanah Laut District, South Kalimantan Province with an area of 700 ha and Musirawas District, South Sumatra Province with an area of 400 ha. The experiment using two planting patterns of rubber clone PB260: (1) single row planting pattern (SR) by 6 x 3 m, and (2) double row planting pattern (DR) by (18 + 2 m) x 2.5 m. The experiment showed that the girth of rubber trees in the SR system at the first tapping year was slightly bigger than that in the DR system, however, it was not statistically significant. The latex yield per tree of SR system was the same as the DR system, however latex yield per hectare of SR system has higher than the DR system, because the SR system have more population than the DR system. The DR system was proved to be a suitable planting system for long-term rubber based intercropping systems.